Narratives of guilt and compliance in unified Germany : Stasi informers and their impact on society - Miller, Barbara, 1969- (Routledge, 1999)
Analysing Stasi files and interviews with one time informers, the author examines the confrontation with this legacy in united Germany. She discusses the daily machinations of the state and the motivation and justification of being an informer.